2018
DOI: 10.5614/j.math.fund.sci.2018.50.3.8
|View full text |Cite
|
Sign up to set email alerts
|

Activity of Caprine CSN1S2 Protein Reducing the COX-2 and IL-17 Expression of Aorta Tissue in Type 2 Diabetes Mellitus Rat

Abstract: Type 2 diabetes mellitus (T2DM) is a degenerative disease that leads to increased inflammation and cyclooxygenase protein production, which causes tissue abnormalities. The aim of this study was to determine the effect of caprine CSN1S2 protein against abnormal metabolic pathways in the aorta of DM rats. The twenty-four-animal model was control, diabetes and treatment groups. Histopathological evaluation of the aortic tissue by hematoxylin eosin staining. The expression of cyclooxygenase and inflammatory cytok… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Systematical effect with potential to progression of PG and correlated with imbalance in the peripheral nerves. In another result also shown that COX-2 gene inactivation protects against diabetes-induced damage in some targeted tissue (Rachmad et al, 2018).…”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…Systematical effect with potential to progression of PG and correlated with imbalance in the peripheral nerves. In another result also shown that COX-2 gene inactivation protects against diabetes-induced damage in some targeted tissue (Rachmad et al, 2018).…”
Section: Resultsmentioning
confidence: 87%
“…The chlorogenic acid has an affinity with the activator side of COX-2 in amino acid residues, which bind with a hydrogen bond. The inflammation pathway was role by COX-2 such as PI3K, NF-κβ, and Akt was blocked when chlorogenic acid deactivated COX-2 by interaction on (active side domain of COX-2) (Rachmad et al, 2018). COX-2 is a central enzyme in the biosynthesis of prostaglandins.…”
Section: Resultsmentioning
confidence: 99%
“…Interaction ligand and protein had the energy binding of -210.23cal/mol (Table 2). In our previous study, showed that effect of therapeutic nutrition against inflammation has a negative effect on COX-2 activity [22]. COX-2 blocking has a serious effect on tissue improvement.…”
Section: Resultsmentioning
confidence: 94%